The Crime Of Having An Abortion Without Indication Of A Medical Emergency And Pregnancy Due To Rape (Decision Study Number 170 / Pid.Sus / 2019 / PN Bau) - Fredy, Fredy; Ruslan, Ruslan; Nurhayati, Nurhayati (Legalpreneur Journal, 2025)
Abortion is a social phenomenon that is becoming more and more alarming every day. A pregnant woman out of wedlock is forced to choose an abortion related to 12 reasons both internal and external underlying. Although the fetus belongs to the woman who is carrying it, abortion or the murder of the womb committed by herself is an act that is punishable, provided for in Article 346 of the Criminal Code. The judge in deciding the case of abortion cases in addition to paying attention to the provisions written in the law in order to fulfill the purpose of the conviction to provide a deterrent effect and improve, also uses his conscience based on a sense of Community Justice. The purpose of this study is to analyze the case study of the decision of the Baubau District Court decision number 170/Pid.Sus / 2019 / PN Bau concerning illegal abortion in accordance with Article 75 of Law Number 36 of 2009 concerning health is connected with the purpose of punishment. This research method uses normative juridical approach. The results showed that even if a woman aborts her own fetus without indication of a medical emergency and as a result of rape, she is punished according to applicable law. The panel of judges in this case has used his conscience considering the mitigating or aggravating circumstances of the defendant. The judge's consideration in giving the verdict has fulfilled the sense of justice and educated the public to avoid illegal abortion.